ALJABAR-C* DAN SIFATNYA - BATKUNDE, HARMANUS; Persulessy, Elvinus R. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2012)
These notes in this paper form an introductory of C*-algebras and its properties. Some results on more general Banach algebras and C*-algebras, are included. We shall prove and discuss basic properties of Banach Algebras, C*-algebras, and commutative C*-algebras. We will also give important examples for Banach Algebras, C*-algebras, and commutative C*-algebras.